Wifedom Mrs Orwell's invisible life - Funder, Anna 1966- (Viking, 2023)
"A riveting work about the woman who sacrificed her future for one of the most famous writers of the twentieth century and a probing look at what it means to be a wife and a writer in the modern world. Looking for wonder and some reprieve from the everyday, award-winning writer Anna Funder slips into the pages of her hero George Orwell. As she watches him create his writing self, she tries to remember her own. When she uncovers his forgotten wife, it's a revelation. Eileen O'Shaughnessy's literary brilliance shaped Orwell's work and her practical common sense saved his life. But why-and how-was she written out of the story? Using newly discovered letters from Eileen to her best friend, Funder recreates the Orwells' marriage, through the Spanish Civil War and the Second World War in London. As she rolls up the screen concealing Orwell's private life she is led to question what it takes to be a writer-and what it is to be a wife. Genre-bending and utterly original, Wifedom is an ode to the unsung work of women everywhere today, while offering a breathtakingly intimate view of one of the most important literary marriages of the twentieth century. It is a book that speaks to our present moment as much as it illuminates the past"--
Keywords: Blair, Eileen / 1905-1945 / Marriage; Orwell, George / 1903-1950 / Marriage; Orwell, George - 1903-1950; Authors' spouses / Great Britain / Biography; Authors' spouses; Marriage; Biographies; Great Britain